Evaluation of the validity of the different arms of the ASAS set of criteria for axial spondyloarthritis and description of the different imaging abnormalities suggestive of spondyloarthritis: data from the DESIR cohort. Issue 4 (3rd January 2014) - Moltó, Anna; Paternotte, Simon; van der Heijde, Désirée; Claudepierre, Pascal; Rudwaleit, Martin; Dougados, Maxime
Abstract : Background: The Assessment of Spondyloarthritis International Society (ASAS) criteria for axial spondyloarthritis (SpA) allows classification of patients with ('imaging' arm) and without ('clinical' arm) imaging abnormalities of the sacroiliac joints. Objective: To compare the phenotype of early axial SpA with regard to the two arms of the ASAS axial SpA criteria. Methods: Demographics, clinical and biological features of SpA, disease activity, severity parameters, and imaging abnormalities at the sacroiliac and spine levels were compared, in the two arms of the ASAS axial SpA criteria, in the patients of the French cohort of early SpA. Results: Of the 615 patients analysed, 435 (70.7%) met the ASAS criteria (262 (60.2%) and 173 (39.8%) in the imaging and clinical arms, respectively). There were no major differences in the characteristics of the two groups except that those in the imaging arm were more likely to be younger, male and have higher concentrations of C-reactive protein. Imaging abnormalities other than those meeting the ASAS criteria for the imaging arm (ie, x-ray-determined structural damage or MRI-revealed inflammatory changes in the sacroiliac joint (SIJ)) were observed (MRI–SIJ structural damage (55.0% vs 3.5%), MRI–spine inflammatory changes (35.1% vs 12.9%), MRI–spine structural damage (10.3% vs 5.3%) and x-ray–syndesmophytes (11.8% vs 5.3%)) in the imaging versus clinical arm, respectively. Conclusions: Our study confirms the external validity of the clinical arm of the ASAS criteria. It is notable that many patients in the clinical arm showed other imaging changes in SIJs and spine.